1997
DOI: 10.1172/jci119596
|View full text |Cite
|
Sign up to set email alerts
|

Association of angiotensinogen gene T235 variant with progression of immunoglobin A nephropathy in Caucasian patients.

Abstract: Genetic variability in the renin-angiotensin system may modify renal responses to injury and disease progression. We examined whether the M235T polymorphism of the angiotensinogen (AGT) gene, the insertion/deletion polymorphism of the angiotensin-converting enzyme (ACE) gene, and the A 1166 → C polymorphism of the angiotensin II type 1 receptor gene may be associated with disease progression in 168 Caucasian patients with IgA nephropathy. All patients had serial measurements of their creatinine clearance, prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
77
7
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(106 citation statements)
references
References 41 publications
(57 reference statements)
20
77
7
2
Order By: Relevance
“…Moreover, in the stratified analysis relating to ethnicity, our results indicated that the A1166C polymorphism was not associated with IgAN risk in Asians. However, as only one paper involving a Caucasian population was identified (Pei et al, 1997), further studies focusing on Caucasian patients should be carried out in future. No publication bias was evident in this meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in the stratified analysis relating to ethnicity, our results indicated that the A1166C polymorphism was not associated with IgAN risk in Asians. However, as only one paper involving a Caucasian population was identified (Pei et al, 1997), further studies focusing on Caucasian patients should be carried out in future. No publication bias was evident in this meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, five studies published between 1997 and 2013 were included in our meta-analysis (Pei et al, 1997;Maruyama et al, 2001;Lau et al, 2004;Huang et al, 2010;You et al, 2013), incorporating 579 IgAN cases and 483 controls (Figure 1). One involved Caucasian subjects (Pei et al, 1997), while four focused on Asian populations (Maruyama et al, 2001;Lau et al, 2004;Huang et al, 2010;You et al, 2013). The countries in which these investigations were carried out included Canada, Japan, Singapore, and China.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Polymorphic variations in the human AGT gene have been shown to be associated with 18 an increased risk of essential hypertension, [18][19][20][21][22] and a decline in renal function. 23 Although it is possible that the AGT gene polymorphisms influence gemcitabine PK through yet unknown mechanisms, the result and the suggested hypothesis in our study should be evaluated both in replication study using another sample set and also in biological functional analyses. Many biomedical researchers have used the KruskalWallis test for finding significant SNPs, and visually checked PK-genotype response patterns.…”
Section: Discussionmentioning
confidence: 81%
“…7). Studies have found that the DD genotype is associated with a more rapid loss of renal function in diabetic nephropathy, 23 IgA nephropathy 24 and adult polycystic kidney disease, 25 when compared to the II or DI genotypes. The genotype does not appear to initiate or cause renal disease per se; rather it is associated with more rapid loss of renal function after disease development.…”
Section: Discussionmentioning
confidence: 99%